Primerjava dveh načinov odvzema mere za ležišče s popolnim stikom za protezo po nadkolenski amputaciji - Erzar, Dominik (Rehabilitacija (Ljubljana), 2016)
Background: The prerequisite for a good prosthetic socket is proper and accurate casting. The aim of our study was to compare sockets made by casting with plaster of Paris and by the Center for International Rehabilitation (CIR) system. Methods: Persons after transtibial amputation who were able to walk with their prosthesis for at least 500 meters, had no wounds on the stump and were willing to participate were included into the study. All the participants were casted by plaster of Paris and the CIR system. For both casting methods we measured casting time, time for cast rectification, number of required corrections, antero-posterior (AP) and medio-lateral (ML) measure, knee circumferences at the patellar-tendon-bearing level, head of fibula and at the end of the stump. We also measured length of the stump. Results: Casting time and rectification time were statistically significantly shorter with the CIR system (p < 0.001 and p = 0.002, respectively) than with plaster of Paris. Fewer cast rectification were needed with the CIR system (3.25 rectifications with CIR on average and 3.88 rectifications with plaster of Paris on average). All other measures were statistically significantly different from the measurements of the stump. The sockets made by casting with plaster of Paris were statistically significantly more comfortable (p < 0.001). Conclusion: Casting time and rectification time were shorter with the CIR system, but the sockets produced using this system were less comfortable.
Keywords: nadkolenska amputacija; nadkolenska proteza; protezno ležišče; socket; transtibial amputation; transtibial prosthesis